2021
DOI: 10.1038/d41586-021-03717-7
|View full text |Cite
|
Sign up to set email alerts
|

The origins of ovarian cancer

Abstract: fter Ana Castillo underwent a double mastectomy two years ago, she had one question for her doctors: "What's the next step?"Castillo carries an altered form of a gene known as BRCA2 that makes her 3-5 times more likely than the general population to develop breast cancer, and between 9 and 14 times more likely to get ovarian Risk-reducing surgery to remove the fallopian tubes and ovaries is performed on people with ovarian cancer risk genes, such as BRCA2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These nucleosomes circulate for a period of one to three hours before being removed by phagocytic cells and other cells. Necrosis, on the other hand, occurs when cells are damaged or stressed to the point of uncontrolled death, leading to the random and incomplete digestion of DNA ( 9 11 ). It has been suggested that the fragmentation profile of circulating cfDNA may reveal information about the tissue origin in cancer patients ( 11 ).…”
Section: Liquid Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These nucleosomes circulate for a period of one to three hours before being removed by phagocytic cells and other cells. Necrosis, on the other hand, occurs when cells are damaged or stressed to the point of uncontrolled death, leading to the random and incomplete digestion of DNA ( 9 11 ). It has been suggested that the fragmentation profile of circulating cfDNA may reveal information about the tissue origin in cancer patients ( 11 ).…”
Section: Liquid Biopsiesmentioning
confidence: 99%
“…Necrosis, on the other hand, occurs when cells are damaged or stressed to the point of uncontrolled death, leading to the random and incomplete digestion of DNA ( 9 11 ). It has been suggested that the fragmentation profile of circulating cfDNA may reveal information about the tissue origin in cancer patients ( 11 ). Additionally, DNA methylation patterns are known to be tissue-specific, and thus, their analysis may allow for the determination of the origin of cf-DNA fragments.…”
Section: Liquid Biopsiesmentioning
confidence: 99%
“…HGSOC is traditional thought to development from ovarian surface epithelium (Ducie et al, 2017). Since the late 1990s, accumulating evidence indicates that HGSOC originates from fallopian tube secretory epithelial cells (DeWeerdt, 2021; Przybycin et al, 2010). However, recent studies demonstrate that both fallopian tube and ovarian surface epithelium are origin of HGSOC (Lohmussaar et al, 2020; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%